Contribuição ao conhecimento químico de Calliandra mucugeana e Calliandra sessilis - Silva, Wildson Max Barbosa da (2012)
This work describes the chemical investigation of Calliandra sessilis and Calliandra mucungeana (Fabaceae). The Chemical prospection of the root extracts of the two species resulted in the isolation and characterization of steroids, diterpenes and fatty esters. From the hexane extract were isolated a ternary mixture of the steroids β-sitosterol, espinasterol and estigmasterol, the pentacyclic triterpene lupeol, besides a diterpene of skeleton cassane, 2,12-dioxo-3- hydroxy-15,17-epoxy-cassa-13(15),14(17)-diene. From the ethanol extract were isolated a binary mixture of bis-(2,3-dihydroxypropil) tetracosanodioate and bis-(2,3- dihydroxypropil) docosanodioate, as well as, a glucosidal steroidal mixture constituted of β-sitosterol, espinasterol and estigmasterol. The structural determinations of isolated compounds were performed by spectrometric techniques, such as: infrared (IR), mass spectrometry (IES-MS) and proton nuclear magnetic resonance (1H NMR) 13-carbon ( 13C NMR), including dimensional techniques (COSY, HSQC and HMBC), besides comparison with described data